Overall stabilization of underground workings in limestone-shells - Mitinskiy, Vasiliy; Chepelev, Valentyn; Vynnykov, Yuriy; Lartseva, Іryna; Aniskin, Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2018)
The characteristic properties of limestone-shell used as the base of foundation are described. Using the example of multi-storey residential building design, comprehensive solution has been proposed for plugging workings in an array of limestone-shell for the subsequent construction of slab-pile foundation, which includes engineering and geological surveys, geotechnical design, the choice of mortars and their compositions, as well as continuous monitoring plugging conditions. It is stated that two types of cement-sand mortar are used for plugging workings: the first is with the addition of superplasticizers, which provide high solution mobility, low water loss and non-shrinkage after hardening; the second is without adding superplasticizers with fluidity high degree. The results of laboratory studies to select the composition of soil-cement are given.
Keywords: limestone-shell; underground working (catacomb); plugging; injection; soil-cement; bearing capacity